An exploratory study of older persons' perceptions of engaging in line dancing classes. Issue 2 (2nd April 2020) - Owen-Booth, Bethan; Lewis, Elenid
ABSTRACT: With the population of older adults expected to continue growing, understanding the benefits of leisure occupations will be vital in facilitating their active engagement. Line dancing is one such leisure occupation. A small, qualitative study was undertaken to identify the perceived benefits of engaging in line dancing. Semi structured interviews were conducted with four female participants aged 65-87 years. A deductive approach to content analysis was employed using the framework of the Canadian Model of Occupational Performance and Engagement. The participants reported that line dancing offered an opportunity for meaningful occupation in retirement and had positive outcomes for their physical health, mood, cognition, and spirituality. These findings corroborate existing evidence supporting engagement in active leisure occupations as key to promoting the mental health and well-being of older adults.